Relationship of different domains of physical activity practice with health-related quality of life among community-dwelling older people: a cross-sectional study - Scarabottolo, Catarina Covolo [UNESP]; Cyrino, Edilson Serpeloni; Nakamura, Priscila Missaki [UNESP]; Tebar, William Rodrigues [UNESP]; Canhin, Daniel da Silva [UNESP]; Gobbo, Luis Alberto [UNESP]; Destro Christofaro, Diego Giulliano [UNESP] (Bmj Publishing Group, 2019)
Objective To analyse the association between different domains of physical activity (PA) and health-related domains of health-related quality of life (HRQoL) in older adults, independent of confounding variables. Design Cross-sectional study. Participants In total, 400 individuals 60 years or above were randomly selected to participate in the study. Primary and secondary outcome measures PA was assessed by a questionnaire in three different domains (work/occupational, sports/gym and leisure time) and total PA. The 36-Item Short Form Health Survey was used to evaluate HRQoL. The variables socioeconomic condition, marital status and presence of health professional-diagnosed comorbidities were self-reported. Results The mean age of the sample was 71.5 (+/- 8.4) years, of whom 58% (1)=232) were female. Male older adults showed higher scores of PA in sports, leisure time and in total PA than female adults. Older adults who were more physically active in the work/occupational domain were associated with better scores in functional capacity (OR=1.73, 95% CI 1.02 to 2.93) and general health perception (OR-1.61, 95% C11.02 to 2.56). Those who presented a higher score in the sports/gym domain had heifer scores in functional capacity, even after adjustment for comorbidities (OR=1.72, 95% CI 1.01 to 2.96). Individuals with higher activity in leisure time were more likely to have better scores in functional capacity (OR=1.75, 95% C11.03 to 2.98), body pain (OR=1.74, 95% CI 1.09 to 2.78) and mental health (OR=1.67, 95% CI 1.03 to 2.69). Older adults who were more active in total PA were 77% more likely to have better scores in functional capacity (OR=1.77, 95% CI 1.04 to 3.02). Conclusion Physically active older adults in the different domains of PA presented better HRQoL parameters, reinforcing the importance of studies analysing PA in different contexts and in countries with low and medium socioeconomic conditions.